Mortality rate of TILAPIA (Oreochromis mossambicus) treated with KASLA (Jathropha curcas) extract. - Buño, Ernesto Jr (UPHSI, 2009)
In grow-out ponds, one problem is the existence of unwated or "wild" fishes. These fishes may compete with the food or mud crabs and shrimps. Because of this, the researchers decided to conduct a study on the effect of J. curcas on the mortality rate of fishes. Kasla (Jatropha curcas) is known to be a very poisonous plant. It is also used as as fish poison. This study aims to determine the mortality rate of tilapia (Oreochromis mossambicus) treated with Kasla. Tilapia fingerlings with the length of 1-1.5 inches were used. The study was done for 48 hours. Each set-up had three replicates and each replicate had 10 fingerlings. Tilapia in every set-up and replicate was chosen randomly. The seeds and fruits were chopped and punced using mortar and pestle. They were combined by water with concentration of 3000 ppm, 6000 ppm and 9000 ppm. Observations were conducted in the 1st, 2nd, 3rd, 6th, 12th, 24th, and 48th hour. The control group was not subjected to the treatment. Our study shows that all the treatments have the same mortality rate, which is 0% in the first twelve hours. There is no significant difference between in Treatment D which is 9000 ppm. Treatment D yields a mortality rate of 10%. The researchers conclude that Kasla is not an effective fish poison since it cannot kill fishes in low concentration.